2010
DOI: 10.1098/rsif.2010.0147
|View full text |Cite
|
Sign up to set email alerts
|

Buckling of sheared and compressed microfibrils

Abstract: In this paper, we study the stability of an initially straight elastic fibril clamped at one end, while the other end is subjected to a constant normal compressive force and a prescribed shear displacement. We found the buckling load of a sheared fibril to be always less than the Euler buckling load. Furthermore, if the end of the fibril loses adhesion, then the buckling load can be considerably less. Our result suggests that the static friction of microfibre arrays can decrease with increasing normal compress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
(45 reference statements)
1
10
0
Order By: Relevance
“…Specifically, after a normal preload F N 0 is applied to bring the surfaces into contact, the normal displacement is fixed during shear. As pointed out in our recent work, fibres in the array can buckle during shear if the normal load is fixed during shear (Nadermann et al 2010). In general, buckling will cause the fibres to detach and will lower the static friction (Shen et al 2009).…”
Section: Introductionmentioning
confidence: 76%
“…Specifically, after a normal preload F N 0 is applied to bring the surfaces into contact, the normal displacement is fixed during shear. As pointed out in our recent work, fibres in the array can buckle during shear if the normal load is fixed during shear (Nadermann et al 2010). In general, buckling will cause the fibres to detach and will lower the static friction (Shen et al 2009).…”
Section: Introductionmentioning
confidence: 76%
“…This study is not presented here, but when the bristles are implanted more vertically, buckling becomes very clear (Fig. 13) [60].…”
Section: Discussionmentioning
confidence: 95%
“…Treating a single fibre as an elastica, [54] showed that fibres maintain side contact at zero normal load if the work of adhesion between the fibre and the surface exceeds the elastic energy stored in the deformed fibre. While vertical fibres must have a high aspect ratio to fulfil this criterion [55] , angled fibres require less energy to be sufficiently deformed to make side contact [54] , [56] , [57] . When strong shear forces act on the acanthae, the resulting moment may exceed the level required to bend the acanthae into side contact, so that they maintain surface contact even for zero or negative loads (adhesion).…”
Section: Discussionmentioning
confidence: 99%